Global Financial Stability Report, April 2005 : Market Developments and Issues. (Global Financial Stability Report; Global Financial Stability Report ;, 2005)
The Global Financial Stability Report (GFSR) provides expert and up-to-date analysis of global capital flows that play a critical role in world economic growth and Financial stability. The report focuses on current conditions in global Financial markets, analyzing Financial imbalances and structural issues that could pose risks to stability and sustained market access by emerging market borrowers. Along with the IMF's semiannual World Economic Outlook, the GFSR is a key vehicle for communicating the IMF's multilateral surveillance. The GFSR also draws out the Financial ramifcations of economic imbalances highlighted by the WEO, making it an indispensable companion publication.